Low rectal resection without a diverting stoma - Thakur, Binay; Devkota, Mukti; Li, Zuosheng; Sharma, Amit; Regmi, Yogesh (Nepalese Journal of Cancer, 2017)
Background: A diverting stoma is a usual practice after low and ultralow rectal resections in a fear to minimize the morbidities related to anastomotic leak. We tried to explore not to use a prophylactic diverting stoma and to assess the rate of leak.Methods: Patients undergoing total proctocolectomy (18%)/ low anterior resection of rectum (LAR) (59%)/ ultralow LAR (18%) and intersphincteric LAR (5%) for colorectal adenocarcinoma were analyzed. In all the cases, total mesorectal excision (TME) approach was used. CT/ MRI was used for proper staging and clinically locally advanced tumors were subjected to neoadjuvant chemoradiation (23%). Anastomosis was performed using circular stapler for colorectal or ileorectal anastomosis (94%) and hand-sewn for coloanal anastomosis (6%). Integrity and adequate vascularity of anastomosis was checked using air leak test and excising epiploica at the region of anastomosis.Results: Seventeen patients with mean age of 52 years were analyzed. Mean distance of tumor from the anal verge was 7 cm. Open and Laparoscopic resections were done in 82% and 18%, respectively. Average height of anastomosis was 3.5 cm from the anal verge. Superficial surgical site infection, intraabdominal abscess requiring prolonged intravenous antibiotics and urinary retention were observed in 41%, 6%, and 6%, respectively. There was one anastomotic leak (6%), which led to post operative death of the patient.Conclusion: Low rectal resections may be carried out without a diverting stoma with an acceptable anastomotic leak rate. In a well-performed ileorectal/ colorectal/ coloanal anastomosis with a good vascularity at the site of anastomosis, routine use of diverting stoma may not be justified, though a randomized controlled trial with larger sample is needed.